Feasibility analysis of novel aerodynamic braking system for horizontal axis wind turbines. (2022) - Navin Kumar, B.; Parammasivam, K.M.; Selvaraju, P.N.; Anbalagan, R.
Abstract: Wind energy is an eco-friendly, highly potential and sustainable energy to meet the growing demand for the energy. Wind turbine farms are set-up in the wind potential areas to generate electricity. The wind turbines are designed to function at a rated rpm. The unexpected wind acceleration and high-speed wind drastically increases the wind turbine rotor speed and damage the mechanical drive train shaft, gear box and turbine blade. The control systems are used to control the over speeding of the wind turbine at extreme wind velocity. In this novel methodology it is attempted to manage the rotational speed of the wind turbine aerodynamically by facilitating the chordwise slot or spacing over the wind turbine blade. The slot which is facilitated over the blade alters the pressure distribution between the upper side and lower side of the turbine blade that controls the rotational speed of the wind turbine rotor within the allowable limit. In this approach, the over speeding of the wind turbine blades is effectively controlled without affecting the power generation. Various parameters of the slot or spacing influences the effectiveness of the braking system. In this work, the length of the spacing on the wind turbine blade experimentally optimized.